A quantitative ultrasound approach to estimate bone fragility: A first comparison with dual X-ray absorptiometry. (April 2017) - Pisani, Paola; Greco, Antonio; Conversano, Francesco; Renna, Maria Daniela; Casciaro, Ernesto; Quarta, Laura; Costanza, Daniela; Muratore, Maurizio; Casciaro, Sergio
Highlights: A new ultrasound approach for estimating bone fragility was introduced. The new parameter effectively discriminated patients that experienced an osteoporotic fracture. The proposed method could be used to prevent fragility fractures in clinical contexts. Abstract: Aim of this paper was to assess the discrimination power of a novel ultrasound (US) parameter, called the Fragility Score (F.S.), in the early identification of subjects prone to osteoporotic fractures. A total of 102 female patients were recruited: 49 with a recent osteoporotic fracture ("frail" subjects), 53 were controls without fracture history ("non-frail" subjects). All the patients underwent a spinal DXA (dual X-ray absorptiometry) and an abdominal US scan of lumbar vertebrae. Acquired US data were analyzed by a novel algorithm, which calculated the F.S. through spectral and statistical analyses involving both echographic images and corresponding "raw" signals. F.S. showed a good performance in discriminating "frail" from "non-frail" subjects (sensitivity = 76%, specificity = 68%), resulting even slightly more effective than DXA-measured BMD (sensitivity = 73%, specificity = 66%). This methodology has a potential to become an effective tool for the early identification, and timely treatment, of "frail" subjects.